The mediating role of psychological resilience in the relationship between frailty and self-efficacy among dialysis patients - Jiang, Su Fang; Wang, Kang Ning; Zhang, Shan; Zhang, Yu Rong; Dong, Man Zhen; Li, Qi Qi; Zhang, Nan Hui; Lin, Juan Juan; Rao, Long Hua (Frontiers in Psychiatry, 2026)
BackgroundFrailty poses a substantial challenge for patients with hemodialysis (HD), influenced by a multitude of personal and social factors. Building on the theory of Hobfoll’s Conservation of Resources (COR) theory, this study sought to evaluate the correlation between frailty and self-efficacy, as well as psychological resilience among patients undergoing HD treatment.MethodsA cross-sectional study was conducted on 397 HD patients at various hospitals in Xiangyang City, Hubei Province, China. Data was gathered between February and May, 2024 using the Frail Scale, the Connor-Davidson Resilience Scale (CD-RISC), and the self-efficacy scale. The collected data were analyzed using SPSS software, applying both descriptive and inferential statistical methods, as well as conducting mediation effect analysis and structural equation modeling with bootstrapping by Amos 26.0.ResultsThe study revealed that the prevalence of pre-frailty and frailty was 26.2% and 38.3%, respectively. The self-efficacy score of the patients was 6.5 (5.0, 8.2) on a scale from 0 to 10. Additionally, the psychological resilience score was 23.0 (20.0, 30.0) on a scale from 0 to 40. The results indicated correlations among psychological resilience, frailty, and self-efficacy in HD patients. Frailty had a negative correlation with self-efficacy (r = -0.166, p < 0.01) and psychological resilience (r = -0.222, p < 0.01). Conversely, self-efficacy and psychological resilience were positively related (r = 0.287, p < 0.01). Psychological resilience, acting as a mediating factor, exhibited an indirect effect size of 35%, while the direct effect size of patient frailty was 65%.ConclusionThe findings of this study underscore a negative association between frailty and self-efficacy. Furthermore, psychological resilience plays an acceptable mediating role in the relationship between frailty and self-efficacy.